Fucosphere - New microsphere carriers for peptide and protein delivery: Preparation and in vitro characterization - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2006)
Purpose: Fucoidan is a complex polysaccharide containing sugars and high amounts of sulphate derived from marine brown algaes. In this study, a new microsphere-delivery system based on cross-linking of fucoidan with chitosan, named Fucosphere, was evaluated as a drug carrier. Bovine serum albumin (BSA) was used as a model protein. The effect of fucoidan (1.5, 1.75, 2.0 and 2.5%), chitosan (0.25, 0.50 and 0.75%) and protein (0.25, 0.50 and 0.75%) concentrations, the origin of chitosan and the preparation methods of the particles on the microsphere characteristics were evaluated. Methods: The microspheres were prepared by a simple method based on the cross-linking of the opposite charged biopolymers. The shape and surface morphologies of the particles were evaluated by scanning electron microscopy (SEM) and the size, charge and encapsulation capacity of the microspheres were determined. The released amount of BSA from the microspheres into phosphate buffered saline (PBS pH 7.4) was determined spectrophotometrically by the Bradford method. SDS-PAGE was performed to check the structural integrity of BSA after the preparation. Results: Smooth and spherical microspheres between the size ranges of 0.61-1.28 mu m were obtained. BSA was efficiently encapsulated into the microspheres (51.8 - 89.5%). All formulation parameters affected the encapsulation capacity of Fucosphere (p < 0.05). The highest encapsulation was obtained with microspheres containing 2.5% of fucoidan (89.5%). Conclusions: The extent of drug release from the microspheres was dependent on the concentrations of polymers and BSA, chitosan origin and type of preparation method. When the addition methods of protein compared, BSA encapsulated into Fucosphere released slower than the adsorbed protein (E) (p < 0.05). The electrophoretic mobility values of Fucospheres changed between +6.9 and +32.3 mV. In general, BSA release from Fucosphere showed a three-phasic release curve. In conclusion, this new fucoidan microsphere system may be a potential delivery of macromolecular drug such as peptide and protein.
Keywords: fucoidan; chitosan; controlled release; protein; microsphere; TREATED ALGINATE BEADS; CONTROLLED-RELEASE; CHITOSAN MICROSPHERES; SUSTAINED-RELEASE; BROWN-ALGAE; MICROCAPSULES; DRUG; SYSTEMS